Viscoelastic and adhesion properties of hot-melts made with blends of ethylene-co-n-butyl acrylate (EBA) and ethylene-co-vinyl acetate (EVA) copolymers. (January 2019) - Moyano, María Alejandra; París, Rodrigo; Martín-Martínez, José Miguel
Abstract: Several hot-melts (HMAs) were prepared by using blends of ethylene-co-n-butyl acrylate (EBA) and ethylene-co-vinyl acetate (EVA) copolymers - EBA/EVA. HMAs were prepared with mixtures of EVA copolymers with 18 (EVA18) and 27 (EVA27) wt% vinyl acetate contents and EBA copolymer with 27 wt% n-butyl acrylate, polyterpene resin and mixture of microcrystalline and Fischer-Tropsch waxes. HMAs made with EBA/EVA blends showed lower viscosities and reduced shear thinning than the ones made with EBA or EVA due to differences in compatibility, but both the set time and the open time were not affected as they depended mainly on the wax nature and amount. The increase of the vinyl acetate (VA) content in EVA copolymer reduced the crystallinity of the EBA/EVA blends. Even EBA copolymer was more compatible with EVA27 than with EVA18 (the α- and β-transitions shown in DMTA plots were closer) and the compatibility did not vary with the EBA content in the blends. The addition of polyterpene resin and the mixture of waxes decreased the compatibility of the EBA/EVA blends, the higher compatibility was observed for the HMAs made with only one copolymer. The tack of the HMAs depended on their EBA/EVA contents, EBA/EVA27 HMAs showed broader temperature interval with higher tack, while the tack of EBA/EVA18 HMAs blend decreased and the temperature interval with tack was shortened and shifted to lower temperatures. Adhesion to polypropylene film was improved in HMAs made with 75 wt% EBA/25 wt% EVA18 and 50–75 wt% EBA/50-25 wt% EVA27. The adhesion to aluminum film of EBA or EVA hot melts was improved only in the joints made with EBA/EVA 27 HMAs, more noticeably when they contained higher EBA content.